2010
DOI: 10.1016/j.aap.2009.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Age-related declines in car following performance under simulated fog conditions

Abstract: The present study examined age-related differences in car following performance when contrast of the driving scene was reduced by simulated fog. Older (mean age of 72.6) and younger (mean age of 21.1) drivers were presented with a car following scenario in a simulator in which a lead vehicle (LV) varied speed according to a sum of three sine wave functions. Drivers were shown an initial following distance of 18m and were asked to maintain headway distance by controlling speed to match changes in LV speed. Five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 45 publications
(54 reference statements)
1
21
0
Order By: Relevance
“…The presence of fog can reduce not only the visibility but also the visual field. Previous studies have confirmed that drivers tend to perform safety-related adaptations, such as reducing speed, to compensate for the insecurity arising from the limited visual field (Ni et al, 2010;Broughton et al, 2007). In this study, drivers reduced their speed significantly in the heavy fog condition on the straight road segment.…”
Section: Effect Of Fog Conditionssupporting
confidence: 61%
See 1 more Smart Citation
“…The presence of fog can reduce not only the visibility but also the visual field. Previous studies have confirmed that drivers tend to perform safety-related adaptations, such as reducing speed, to compensate for the insecurity arising from the limited visual field (Ni et al, 2010;Broughton et al, 2007). In this study, drivers reduced their speed significantly in the heavy fog condition on the straight road segment.…”
Section: Effect Of Fog Conditionssupporting
confidence: 61%
“…Fog as a type of inclement weather, has an enormous negative influence on drivers' visibility, which causes quite a change in driving behavior. Previous studies of driving behavior in fog have focused on drivers' car following performance (Broughton et al, 2007;Kang et al, 2008;Ni et al, 2010), collision avoidance performance (Ni et al, 2012;Mueller and Trick, 2012) and behavior/responses to road sign instructions (Hassan and Abdel-Aty, 2011;Trick et al, 2010). However, little research has investigated how drivers perform on roads with complex alignments such as S-curves when driving in fog.…”
Section: Influence Of Fog On Driving Behavior and Safety On Curvesmentioning
confidence: 97%
“…One interesting topic for future research is to examine whether driving performance can improve by changing scan strategies. On a related issue, previous research found age-related decrement in performance in a car following task (Ni, Kang & Andersen, 2010). Another topic for future research is to examine whether age-related decrement in driving tasks could be predicted by an age-related difference in eye movement patterns, and whether we could improve older drivers' performance by training them to use a different scan strategy.…”
Section: Discussionmentioning
confidence: 99%
“…These tasks include steering control (Wallis, Chatziastros, Tresilian & Tomasevic, 2007), braking (Fajen, 2005), car following (Ni, Kang & Andersen, 2010), and collision detection (Ni & Andersen, 2008). Previous studies have shown that observers' ability to attend and process information in a visual scene is very limited (Rensink, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several research teams are examining older drivers (e.g. Freund & Colgrove, 2008;Freund et al, 2005aFreund et al, , 2005bHarvey et al, 1995;Hoffman & McDowd, 2010;Lee et al, 2002;Ni et al, 2010;Szlyk et al, 2002). In addition, researchers are using simulators to examine the impact of roadway design among older and younger drivers (e.g., Shechtman et al, 2007), or the impact of new technologies on different driving populations (e.g., Martin & Elefteriadou, 2010).…”
mentioning
confidence: 98%